Bond position function between corroded reinforcement and recycled aggregate concrete using beam tests. (30th November 2016) - Yang, Haifeng; Deng, Zhiheng; Ingham, Jason M.
Highlights: The bond rigidity linearly decreases in the middle of the anchorage length. Increasing the RCA substitution rate had little effect on the bond position curves. The bond rigidity becomes more uniform as crack widths increase. The bond position function between corroded rebar and RAC is suggested. Abstract: Twelve beam tests were carried out in order to investigate the bond strength and bond position function between corroded rebar and recycled aggregate concrete (RAC), with the electrochemical method adopted to accelerate steel corrosion. Three recycled coarse aggregate (RCA) replacement percentages (i.e., 0%, 50% and 100%) and 4 expected corrosion crack widths of RAC (i.e., 0 mm, 0.05 mm, 0.3 mm, and 0.6 mm) were considered. Test data was used to calculate the bond stress along the anchorage length, and the influence of both RCA replacement percentages and the corrosion cracking widths on the bond strength and bond position function between the RAC and rebar. The bond position functions for different corrosion levels of reinforced RAC were also established. The results indicated that the ultimate bond strength of reinforced RAC beams decreased overall with an increase of the RCA replacement percentage and corrosion crack width, but that the rate of decline reduced with an increase of RCA and corrosion level. The bond position curve of the reinforced RAC beams was similar to that of natural aggregate concrete (NAC) beams subjected to bending and shear stresses before and after steel corrosion, with a sharp increase of the relative bond stiffness at both anchorage ends, and an almost linear decrease of relative bond stiffness in the range of 0.15–0.85 times the anchorage length. Increasing the RCA substitution rate had little effect on the bond position curves, and the bond distribution became more uniform as the crack widths increased.